Factors Analysis of Job Satisfaction at XYZ Company - Gustiawan, Feri; Moeins, Anoesyirwan; Marhalinda, Marhalinda (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to identify and analyze the factors that affect Job Satisfaction in XYZ company, through the variables of Serving Leadership and Work Motivation. This study uses a quantitative method by involving a saturated sampling technique based on certain criteria so that all employees in company XYZ become a research sample of 32 people. Furthermore, data was collected through a questionnaire processed with relevant statistical methods, namely multiple linear regression tests with the JASP 0.18.3.0 (2024) data processing software application. The results of this study show that: (1) Serving Leadership (X1) has a positive and significant effect on Job Satisfaction with the value of tcount > t table tcount > t table (20.100 > 2.04227) with prob. Sig < 0.05 (< 0.05). (2) Work Motivation (X2) has a positive and significant effect on Job Satisfaction with a ttable > ttable value (10.966 > 2.04227) with prob. Sig < 0.05 (< 0.05).